2011
DOI: 10.1371/journal.pone.0017059
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Consequences of an Extreme Mountain Ultra-Marathon

Abstract: We investigated the physiological consequences of one of the most extreme exercises realized by humans in race conditions: a 166-km mountain ultra-marathon (MUM) with 9500 m of positive and negative elevation change. For this purpose, (i) the fatigue induced by the MUM and (ii) the recovery processes over two weeks were assessed. Evaluation of neuromuscular function (NMF) and blood markers of muscle damage and inflammation were performed before and immediately following (n = 22), and 2, 5, 9 and 16 days after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
274
3
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(321 citation statements)
references
References 45 publications
35
274
3
9
Order By: Relevance
“…Further evidence is the fact that TC was not significantly elevated at any post-stage or post-race time-point, but was reduced after S1 (p<0.001), confirming previous findings of reduced swelling and a post-race decrease in muscle mass. 16 The low systemic markers of muscle damage and inflammation, when compared with previous findings following the Comrades Marathon 16 confirm the findings of Millet et al 1 who, in their study on the neuromuscular consequences of extreme running in a 166 km mountain ultra-marathon, reported that post-race serum concentrations of CPK, hsCRP and neutrophils were lower than those measured after a road race with similar finishing times. 1 These researchers attributed their findings of low concentrations of systemic markers of muscle damage and inflammation to the relatively soft underfoot surfaces and to the athletes frequently being forced to walk, jump and climb due to the technical demands of the terrain.…”
Section: Discussion Evidence Of Muscle Damage and Inflammationsupporting
confidence: 81%
See 2 more Smart Citations
“…Further evidence is the fact that TC was not significantly elevated at any post-stage or post-race time-point, but was reduced after S1 (p<0.001), confirming previous findings of reduced swelling and a post-race decrease in muscle mass. 16 The low systemic markers of muscle damage and inflammation, when compared with previous findings following the Comrades Marathon 16 confirm the findings of Millet et al 1 who, in their study on the neuromuscular consequences of extreme running in a 166 km mountain ultra-marathon, reported that post-race serum concentrations of CPK, hsCRP and neutrophils were lower than those measured after a road race with similar finishing times. 1 These researchers attributed their findings of low concentrations of systemic markers of muscle damage and inflammation to the relatively soft underfoot surfaces and to the athletes frequently being forced to walk, jump and climb due to the technical demands of the terrain.…”
Section: Discussion Evidence Of Muscle Damage and Inflammationsupporting
confidence: 81%
“…1 The sporadic increases in intensity of effort, rises in T intest , substantial body mass loss and increases in serum osmolality during the event, did not confirm previous suggestions 3,4,11 that thermal and hydration status is directly related to the degree of muscle damage. It would be of interest to the investigate the impact of pre-race preparation on markers of muscle damage and inflammatory response found following this multi-day trail running event and to control the nutritional and fluid intake in future field work on multiday trail running.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Other examples can be found in (1) training adaptations which can be evidenced by ES often combined with voluntary contractions and EMG measurements (Van Cutsem et al 1998) or (2) fatigue in athletes. Another example is the fact that extreme running (over 24 h) induces large central fatigue and changes at the muscle level that are highly variable and dependent on the course proWle and muscle group (Martin et al 2010;Millet et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These changes may contribute to attenuate the potentially harmful eccentric phase and overall load faced by their musculo-skeletal system at each step (Morin et al 2011a, b), which may not be an issue of importance during exhaustive runs of shorter durations. Further support to this hypothesis was given by the absence of correlation observed between the changes in running pattern and the large losses of force (maximal voluntary contraction, MVC) observed in the knee extensors and plantar flexors (Martin et al 2010;Millet et al 2011). Furthermore, the changes in running pattern reported after ULD were very consistent (a) with an overall decrease in the amplitude of oscillation of the spring-mass system at each step, and (b) with changes reported in particular situations where an impairment of muscular function and/or structure and/or localized pain was induced by a muscular biopsy of the vastus lateralis (Morin et al 2009a) or by the natural ageing process (Cavagna et al 2007;Karamanidis and Arampatzis 2005).…”
Section: Introductionmentioning
confidence: 99%